2019
DOI: 10.1080/22221751.2019.1568179
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics comparisons of p -aminosalicylic acid (PAS) resistance in folC mutated and un-mutated Mycobacterium tuberculosis strains

Abstract: p -Aminosalicylic acid (PAS) is an important second-line antibiotic for treating multidrug-resistant tuberculosis (MDR-TB). Due to gastrointestinal disturbance and intolerance, its potent and efficacy in the treatment of extensively drug-resistant (XDR)-TB commonly are poor. Thus, it is important to reveal the mechanism of susceptibility and resistance of Mycobacterium tuberculosis (Mtb) to this drug. Herein, we screened and established PAS-resistant (PAS r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…Very recently, researchers found that in PAS-resistant clinical isolates of M. tuberculosis with folC mutation, protein expression levels of folP2 were significantly lower than in strains with no folC mutation 28 . Though FolP2 of M. tuberculosis has been predicted to be defective in dihydropteroate synthesis activity 27 , deletion of the folP2 gene in M. smegmatis resulted in increased susceptibility to SMX 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, researchers found that in PAS-resistant clinical isolates of M. tuberculosis with folC mutation, protein expression levels of folP2 were significantly lower than in strains with no folC mutation 28 . Though FolP2 of M. tuberculosis has been predicted to be defective in dihydropteroate synthesis activity 27 , deletion of the folP2 gene in M. smegmatis resulted in increased susceptibility to SMX 26 .…”
Section: Discussionmentioning
confidence: 99%
“… 35 The integromics data analysis is also performed to reveal the MTB resistance mechanism due to p-aminosalicylic acid for MDR-TB and XDR-TB treatment. 36 …”
Section: Methodsmentioning
confidence: 99%
“…Many excellent reviews report the genetic mechanisms involved in this resistance to RIF, INH, KM, CP and other drugs [18,23,24,98,118,126]. [106,107] ubiA Phosphoribosyltransferase (cell wall synthesis) [108,109] DLM ddn Deazaflavin (F 420 )-dependent nitroreductase (mycolic acid synthesis) [110] fgd-1 Glucose-6-phosphate dehydrogenase (F 420 synthesis) [110] fbiA Protein FbiA (F 420 synthesis) [110] fbiB Protein FbiB (F 420 synthesis) [110] fbiC Protein FbiC (F 420 synthesis) [110] PZA pncA Pyrazinamidase (conversion of PZA into pyrazinoic acid, resulting in dysfunctions of membrane potential) [98,111] ethA Monooxygenase (activation of ETO and PTO) [19,122] mymA Monooxygenase (activation of ETO and PTO) [121,123] katG Catalase-peroxidase (activation of ETO, PTO, INH) [122] inhA Enoyl-ACP reductase (mycolic acid synthesis) [98,122] PAS thyA Thymidylate synthase [23,124] folC Dihydropholate synthase [23,125] dfrA Dihydropholate reductase [23,125] Phenotypic testing is still considered a gold standard for Mtb DST, which is accurate, but takes at least two weeks for results [98]. However, a pivotal role has been recently played by the more and more rapid molecular methods to diagnose drug-resistant TB by the identification of chromosomal mutations, including line probe assays, the Xpert MTB/RIF system (Cepheid, Sunnyvale, CA, USA), target gene sequencing, whole genome sequencing (WGS), point-of-care nucleic acid amplification devices [9,127,128].…”
Section: Acquired Drug-resistance Of Mtbmentioning
confidence: 99%